2020
DOI: 10.1007/s13659-020-00232-6
|View full text |Cite
|
Sign up to set email alerts
|

A New Epi-neoverrucosane-type Diterpenoid from the Liverwort Pleurozia subinflata in Borneo

Abstract: New bioactive 13-epi-neoverrucosane diterpenoid, 5β-acetoxy-13-epi-neoverrucosanic acid (1) along with three known secondary metabolites, 13-epi-neoverrucosan-5β-ol (2), chelodane (3) and (E)-β-farnesene (4) were isolated from the MeOH extract of east Malaysia's liverwort Pleurozia subinflata. The chemical structure of new compound was elucidated by the analyses of its spectroscopic data (FTIR, NMR and HR-ESI-MS). These epi-neoverrucosane-type compounds seem to be notable chemosystematic markers for P. subinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The newly identified compound 181 showed the strongest activity, with MIC values of 12.5 and 50 μg/ml against L. thermophilum and H. sabahensis , respectively. Among the other identified diterpenoids, 182 and 183 were both moderately active with an MIC value of 100 μg/ml against L. thermophilum ( Kamada et al, 2020 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The newly identified compound 181 showed the strongest activity, with MIC values of 12.5 and 50 μg/ml against L. thermophilum and H. sabahensis , respectively. Among the other identified diterpenoids, 182 and 183 were both moderately active with an MIC value of 100 μg/ml against L. thermophilum ( Kamada et al, 2020 ) .…”
Section: Resultsmentioning
confidence: 99%
“…13-epi-Neoverrucosan diterpene is the epimer of neoverrucosan with the isopropyl group in β configuration at C-13; this compound was first discovered in P. stephensoniana [22]. 13-epi-neoverrucosane-Type diterpenoids were also identified in the liverwort Schistochila nobilis [19], the liverwort Fossombronia alaskana [25], the liverwort Lepicolea ochroleuca [26], the marine sponge Axinyssa tethyoides [21], the liverwort P. subinflata [27], and the marine sponge Hamigera tarangaensis [28]. Few bioactivity assays showed that analogues of 13-epineoverrucosane analogues still failed to inhibit the growth of HL-60 cells at concentrations up to 50 µM [28].…”
Section: Introductionmentioning
confidence: 99%